Nagas as a society against voting : and other essays - Wouters, Jelle J. P. (Nagaland : Highlander Books, 2019)
"The essays in this volume were written over the course of the last five years. They engage a range of subjects, and each can be read on its own, as an independent essay. They, however, converge on certain broad themes and together amount to a treatise on politics and society in Nagaland. I have, for the most part, left the essays in the form in which they originally appeared, although I have sought to correct any errors where appropriate. Consequently, there is some repetition in the observations, arguments, and theoretical overtures between some of the essays, but this could not be avoided without affecting the coherence and contexts of the particular arguments I pursue in each independent essay. Besides a broad thematic convergence, the essays also share a methodological coherence in the sense that they are shaped by ethnography - both as a research method and written form - often spiked with oral and archival histories that contextualize my narratives and arguments. The essays that follow are firmly grounded in the historical experiences and ethnographic specifics of Naga society. At the same time, however, I have tried to speak about larger issues and approaches in the study of democracy and elections, kinship and tribes, and the politics of place and identity. As such, I hope this collection is of interest both to those interested in the specifics of contemporary Naga society and to scholars of Highland Asia, India, political anthropology, and conceptual politics and sociology more widely"-- Provided by publisher
Keywords: Character of Political and Social life, discuss the origins, evolution and convolutions of Naga movement for self determination